Efektifitas Peran BPKP dalam Pembinaan dan Pengawasan Implementasi Sistem Informasi Manajemen Daerah (SIMDA) - Wibisono, Arif Fajar (Jurnal Reviu Akuntansi dan Keuangan)
The purpose of this paper is to analyze the effectiveness of Indonesia’s government internalauditor Badan Pengawasan Keuangan Pembangunan (BPKP) role on supervison dan controllingon implementation aplication Sistem Informasi Manajemen Daerah (SIMDA). This research isa qualitative research by using descriptive analysis and interview with senior auditor in BPKPYogyakarta, he is a coordinator ini goverment accounting region. This result are minimum human resources, the low government budget, and employee are difficult to changing to the newworking method made be the problems in efektiveness of supervison and controling implementation SIMDA. The limitation on this research is only the one kind of supervison and controllingon SIMDA aplication. The future research must be another prosedures supervision and controlling in BPK and more object research.Key words: BPKP, Efektiveness, SIMDA